PENGARUH KOMPONEN KEAHLIAN TERHADAP KEMAMPUAN AUDITOR DALAM PENDETEKSIAN KECURANGAN PADA AUDITOR BPKP SUMATERA BARAT - Fauziah Muchlis; Zulbahridar Zulbahridar; Riska Natariasari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aimed to analyze the effect caused by the auditor’s skill component consist of knowledge component, experience, decision strategies, cognotive abilities, task analysis, and interpesonal skill with auditor’s ability on fraud detection. This study uses total sampling with 80 samples obtained from the all of auditor at BPKP West Sumatera. Data collection techniques in this study is in the form of questionnaires. Number of questionnaires returned was 42, while data analysis technique used is multiple regression analysis were processed with SPSS version 16 for Windows. The result of this research indicated that (1) knowledge component has no effect to the auditor’s ability on fraud detection where significant value 0,174>0,05 and